AKTIVITAS ANTIMIKROBA YOGURT SUSU SAPI YANG DIINKUBASI DENGAN TEMPURUNG KELAPA HIJAU MUDA (Cocos nucifera L. var. viridis Hassk.) - SAPUTRA D. C.; S. A. LINDAWATI; I G. A. A. PUTRA (Majalah Ilmiah Peternakan, 2021)
This study aims to find out the antimicrobial activity of cow’s milk yogurt incubated with a light green coconut shell (Cocos nucifera L. var. viridis Hassk.) against pathogenic bacteria. The experimental design is Completely Randomized Design (CRD) with three treatments and five repeats. The three treatments are: cow’s milk incubated with a jar or control container (P0), cow’s milk incubated with a light green coconut shell without coconut flesh (P1), and cow’s milk incubated with a light green coconut shell containing coconut flesh (P2). The observed variables are antimicrobial activity against pathogenic microbes (Escerichia coli and Staphylococus aureus), total tertitration acid and total lactic acid bacteria. The results showed that the antimicrobial activity of yogurt against Escerichia coli in all treatments (P2, P1, and P0) was obtained with a range of 5.67-5.87 mm statistically no noticeable difference (P>0.05). While against Staphylococus aureus obtained in the range of 6.27-6.46 mm in the treatment of P2 and P1 differ markedly (P<0.05) statistically compared to P0, followed by total titrated acid, and lactic acid bacteria in all treatments (P2, P1, and P0) showed no significant differences (P>0.05) each ranging from 1.62-1.68 %; and 6.6x104-1.4x107 CFU/g. The conclusions of this study showed that the antimicrobial activity of cow’s milk yogurt incubated with a light green coconut shell (Cocos nucifera L. var. viridis Hassk.) against pathogenic bacteria has broad-spectrum antimicrobial activity.